The Strategy of Teaching of Preventing Violence in Cyber Media by Journalism Lecturer of UIN Syarif - Rifki Pratama; Mai Hendar Santoso; Ken Devina (Yayasan Hurriah, Banda Aceh, 2021)
Abstract: The Strategy of Teaching of Preventing Violence in Cyber Media by Journalism Lecturer of UIN Syarif. At this time online media or cyber media is one of the fastest-growing technologies. What was originally only for commercial purposes and information facilities, now online media or cyber has developed as a means of online education. Almost all levels of education in Indonesia carry out teaching and learning activities online especially because of the Covid 19 pandemic, UIN Syarif Hidayatullah Jakarta is no exception. Along with the development of online media technology or cyber media, now violence does not only occur in the real world but can occur in cyber media, such as what happens on social media. This article aims to educate or provide knowledge about strategies to prevent violence in today's cyber media and how effective the learning methods for preventing violence in cyber media are by lecturers at UIN Syarif Hidayatullah Jakarta. This article was created using a questionnaire instrument method, namely a survey conducted on Google Form regarding learning strategies for preventing violence in cyber media by a teacher at UIN Syarif Hidayatullah Jakarta. And of all the people who filled out the survey, almost all agreed that learning strategies for preventing violence in cyber media needed to be carried out. From these results, it can also be interpreted that almost all students who filled out the survey agreed that learning about violence prevention in cyber media needed a strategy so that the education delivered could be effective. to students of UIN Syarif as well as in a wider scope such as the general public. Abstrak: Pada saat ini media online atau media siber adalah salah satu teknologi yang paling cepat perkembangannya.Yang semula hanya untuk kepentingan komersial dan sarana informasi, sekarang media online atau siber berkembang sebagai sarana pendidikan online.Hampir seluruh tingkatan pendidikan di Indonesia melakukan kegiatan belajar mengajar melalui online terlebih karena pandemi covid 19, tak terkecuali UIN Syarif Hidayatullah Jakarta. Seiring dengan berkembangnya teknologi media online atau media siber kini kekerasan tidak hanya terjadi di dunia nyata namun bisa terjadi di media siber, seperti yang terjadi di media social. Artikel ini bertujuan untuk mengedukasi ataupun memberi pengetahuan bagaimana strategi mencegah kekerasan yang ada di media siber sekarang ini dan seberapa efektif metode pembelajaran pencegahan kekerasan di media siber oleh pengajar UIN Syarif Hidayatullah Jakarta. Artikel ini dibuat menggunakan metode instrument kuesioner yaitu dengan survey yang diadakan di google form mengenai strategi pembelajaran pencegahan kekerasan di media siber oleh pengajar UIN Syarif Hidayatullah Jakarta. Dan dari keseluruhan orang yang mengisi survey hampir semua setuju bahwa strategi pembelajaran pencegahan kekerasan di media cyber perlu dilakukan. Dari hasil tersebut juga dapat diartikan bahwa hampir semua mahasiswa yang mengisi survey setuju bahwa pembelajaran pencegahan kekerasan di media siber dibutuhkan strategi agar edukasi yang disampaikan dapat efektif kepada mahasiswa UIN Syarif maupun di lingkup yang lebih luas seperti masyarakat umum